Sustainable development science, management and environment - Harlow, Kane (Callisto Reference, 2015)
The technological improvement of our civilization has established a consumer society growing more rapidly than the planet's resources allow, with the needs for resource and energy rising exponentially in the past century. For the assurance of a secured future for humans, an enhanced comprehension of the environment as well as technological solutions, behaviors and mindsets is important, in accordance with modes of development that the ecosphere of earth can support. Sustainable development provides an approach that would be useful to blend with the managerial strategies and assessment tools for decision and policy makers at the regional planning level. This book focuses on sustainability and its application in life sciences, business and management, and environment.